2016
DOI: 10.1007/s00784-016-1888-y
|View full text |Cite
|
Sign up to set email alerts
|

External root resorption of the second molar associated with mesially and horizontally impacted mandibular third molar: evidence from cone beam computed tomography

Abstract: Given the possibility of ERR associated with third molar impaction, the prophylactic removal of these impacted teeth could be considered especially for those patients with over 35 years and mesially and horizontally impacted teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
66
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 28 publications
13
66
3
6
Order By: Relevance
“…Risk factors (patient's age and impaction depth) for external root resorption have been evaluated 26 but gender was not evaluated. The finding of this study showed gender had no influence on occurrence of external root resorption on the adjacent second molar.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors (patient's age and impaction depth) for external root resorption have been evaluated 26 but gender was not evaluated. The finding of this study showed gender had no influence on occurrence of external root resorption on the adjacent second molar.…”
Section: Discussionmentioning
confidence: 99%
“…The category of impaction of each tooth was identified with presurgical panoramic radiography and/or CBCT scans, and recorded based on Winter’s classifications as described before328. Furthermore, the patient exclusion criteria were listed as follows: 1) the impacted mandibular third molars associated with cystic or tumor lesions, 2) the teeth with less than two thirds of root developed, 3) the teeth showing extensive carious lesion, 4) the adjacent second molars which were extracted or impacted simultaneously, 5) oral surgical procedures involved in the mandibular third molar region, 6) historical or ongoing orthodontic treatments, 7) the poor quality of CBCT images which jeopardized unambiguous view of local anatomy and structures.…”
Section: Methodsmentioning
confidence: 99%
“…These impacted teeth usually result in diverse types of pathological conditions including reiterative pericoronitis, swelling, odontogenic cysts or tumors, bone loss as well as root resorption of the adjacent teeth, thus inevitably leading to impaired oral functions and discomfort123. The extraction of impacted mandibular third molar is one of the most common surgical procedures in the dental clinic and outpatient department of oral and maxillofacial surgery.…”
mentioning
confidence: 99%
“…Occasionally, it is necessary to remove the tooth in order to avoid other problems such as pericoronitis, swelling, odontogenic cysts or tumors, bone loss and external root resorption (ERR) of the adjacent second molar. 1 However, the decision of extracting or maintaining a third molar is controversial. 2 If an impacted third molar is not extracted after a certain stage of its formation, it may contribute to second molar ERR.…”
Section: Introductionmentioning
confidence: 99%
“…2 If an impacted third molar is not extracted after a certain stage of its formation, it may contribute to second molar ERR. 1 According to Tsesis et al 3 ERR is a pathological process that occurs at the permanent tooth outer surface and it may be induced by pulpal infection or periodontal inflammation related causes, or pressure associated with orthodontic movements, impacted tooth or pathoses. Periapical and panoramic radiographies (PR) are the standard imaging modalities for determining third molar characteristics.…”
Section: Introductionmentioning
confidence: 99%